Formation and development of local self-government agencies in Ukraine (1991–2019) - Yu. O. Zahumenna; V. V. Lazarev (Law and Safety)
Local self-government is an integral part of a democratic society, since it actively influ-ences the political and socio-economic conditions for the development of civil society, and becomes an important prerequisite for the creation of a democratic and legal state. The de-velopment of legislative principles of local self-government in the Ukrainian state is influ-enced by the experience of Western standards of local self-government, the practice of state building in Eastern European and other countries. An important factor for the devel-opment of self-government institutions is the process of globalization, which significantly changes socio-political relations, changes the principles of interaction of territorial com-munities, political organizations and local self-government agencies. The authors of the ar-ticle study the current theoretical and methodological, legal and practical aspects of local self-government in Ukraine. The historical regularities of the formation and development of local self-government in Ukraine (1991–2019) are studied. The stages of the formation and reform of local self-government and territorial organization of public power in Ukraine are determined, namely the authors have distinguished three stages: 1990-1996 (formation of the institution of local self-government of independent Ukraine before the adoption of the Constitution); 1996–2014 (development of the Constitutional principles of local self-government); from 2014 to the present day (reform of local self-government of Ukraine, decentralization). The current problems of ensuring the effective functioning of local self-government agencies are studied.